2014
DOI: 10.5152/tjar.2014.75508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spinal Anaesthesia and Paravertebral Block in Unilateral Inguinal Hernia Repair

Abstract: In conclusion, paravertebral block provides acceptable surgical anaesthesia, maintaining good quality and long duration on postoperative analgesia in unilateral hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The fall in hemodynamic responses was substantially lesser in the PVB group when compared to the SAB group, and our findings were consistent with previous studies. [ 6 15 16 ] This might have also resulted in the administration of mephentermine in the SAB group to maintain BP during hypotensive state, also consistent with the previous studies. [ 17 ] Although the sympathetic chain is a part of the paravertebral space, not much hemodynamic variation is noticed in PVB since it is a unilateral anesthetic technique.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The fall in hemodynamic responses was substantially lesser in the PVB group when compared to the SAB group, and our findings were consistent with previous studies. [ 6 15 16 ] This might have also resulted in the administration of mephentermine in the SAB group to maintain BP during hypotensive state, also consistent with the previous studies. [ 17 ] Although the sympathetic chain is a part of the paravertebral space, not much hemodynamic variation is noticed in PVB since it is a unilateral anesthetic technique.…”
Section: Discussionsupporting
confidence: 78%
“…Although not significantly different, SAB group experienced more adverse effects than in the PVB group, similar to the previous findings. [ 15 ] Urinary retention and vomiting were the two complications observed in the SAB group. The blockade of parasympathetic fibers that innervate the autonomic bladder control might be probable reasons behind the adverse effects in the SAB group.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have slow onset and takes longer to reach a peak effect. [ 27 ] Studies have reported time to surgical anesthesia more than 20 min with the use of PVB. [ 28 ] For breast surgery, these values can be significant, so till the peak effect of the block is attained; patient may have already required opioid supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] In our study, none of the patients of Group PVB experienced motor blockade as reported in the previous studies. [ 20 21 ] Therefore, ambulation occurred much earlier in Group PVB than Group SA, in which bilateral motor blockade precludes ambulation until its anesthetic effects completely wear off.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were consistent with those of other studies. [ 4 19 20 ] The time to perform the block was significantly higher in Group PVB (15.79 ± 1.11 min) than Group SA (6.00 ± 0.74 min) because of multiple injections and nerve stimulator-guided technique in Group PVB. The time to surgical anesthesia was significantly higher in Group PVB than Group SA (16.55 ± 2.35 min vs. 8.4 ± 1.43 min) similar to other studies[ 19 ] owing to injections given at multiple levels.…”
Section: Discussionmentioning
confidence: 99%